Platelet soluble CD40L and matrix metalloproteinase 9 activity are proinflammatory mediators in Behçet disease patients - Bello, Ihosvany Fernández; Álvarez, María T.; López-Longo, Francisco J.; Arias-Salgado, Elena G.; Martín, Mónica; Jiménez-Yuste, Víctor; de la Rúa, Ana Rodríguez; Butta, Nora V. (Thrombosis and Haemostasis, 2012)
Platelets are the major source of plasma-soluble CD40L (sCD40L), an important inflammatory mediator. This study explored the impact of platelet-derived sCD40L on Behçet disease (BD), an autoinflammatory vasculitis. We also searched for influences by platelet matrix metalloproteinases (MMP) –2 and MMP-9, implicated in several inflammatory diseases, on CD40L shedding from platelet membrane. Platelet activation were studied by flow cytometry and aggregometry, surface expression of CD40L and platelet-leukocyte aggregates by flow cytometry, sCD40L by ELISA, cellular CD40L and CD40 levels by Western blot and MMPs activity by gelatin zymography. The effect of sCD40L on MMP9 expression was studied in cultured MEG-01 cells. Plasma and platelet-released sCD40L levels were higher in BD patients. No differences in platelet activation and in platelet-leukocyte aggregates formation were observed between BD patients and controls. Plasma and platelet MMP-9 levels were increased in BD patients, whereas there was no difference in platelet MMP-2 activity. Since a correlation between plasma sCD40L and platelet MMP-9 activity was observed, we studied the influence of sCD40L on MMP-9 levels in the megakaryoblastic cell line MEG-01. Treatment of MEG-01 cells with recombinant sCD40L increased MMP-9 but did not change MMP-2 levels. In conclusion, sCD40L release from platelets was mediated by MMP-9, and MMP-9 expression was in turn upregulated by sCD40L in the MEG-01 cell line. We conclude that platelets and megakaryocytes might participate in a positive feedback loop occurring between sCD40L and MMP-9 which would contribute to the proinflammatory state observed in BD.
Keywords: Behçet disease; CD40L; matrix metalloproteinase 9; platelets; MEG-01 cells